2010
DOI: 10.1186/1472-6823-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Low serum creatinine is associated with type 2 diabetes in morbidly obese women and men: a cross-sectional study

Abstract: BackgroundLow skeletal muscle mass is associated with insulin resistance and metabolic syndrome. Serum creatinine may serve as a surrogate marker of muscle mass, and a possible relationship between low serum creatinine and type 2 diabetes has recently been demonstrated. We aimed to validate this finding in a population of Caucasian morbidly obese subjects.MethodsCross-sectional study of 1,017 consecutive morbidly obese patients with an estimated glomerular filtration rate >60 ml/min/1.73 m2. Logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
(42 reference statements)
5
40
1
3
Order By: Relevance
“…These results are consistent with improvement of diabetes and kidney function as observed in other studies [18,22]. Furthermore, previous studies have demonstrated lower serum creatinine levels and increased serum uric acid in STZ-diabetic animals and in type 2 diabetic humans [23]. Similarly, in this work, serum creatinine was lower and uric acid higher in the STZ-diabetic group, which could suggest renal impairments associated with diabetic complications [22].…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with improvement of diabetes and kidney function as observed in other studies [18,22]. Furthermore, previous studies have demonstrated lower serum creatinine levels and increased serum uric acid in STZ-diabetic animals and in type 2 diabetic humans [23]. Similarly, in this work, serum creatinine was lower and uric acid higher in the STZ-diabetic group, which could suggest renal impairments associated with diabetic complications [22].…”
Section: Discussionsupporting
confidence: 81%
“…GFR was markedly increased (Figure 1J, P <0.01), while plasma creatinine level was decreased (Figure 1K, P <0.05), probably secondary to glomerular hyperfiltration. 14 Urinary protein level was unchanged in ObM compared to the lean group (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…Serum creatinine levels are significantly lower in the diabetic patients (9,10). Low serum creatinine levels were associated with type 2 DM in a recent study of nonobese middle-aged Japanese men (11), leading to the hypothesis that low creatinine might reflect low muscle mass volume (12,13). Low serum creatinine may also be related to significantly higher estimated GFR (eGFR) when calculated based on serum creatinine.…”
mentioning
confidence: 99%